Effect of la 2O3 addition on electrical properties of PZN-PZT based ceramics - Tanabat Promjun (2018)
In this study, compositions in the 0.2Pb(Zn1/3Nb2/ 3)O3-0.8Pb(Zr1/2Ti1/2)O3 based systems will be developed based on the material engineering approach (processing vs. electrical properties). This work involves the fabrication of high purity PZN-PZT based in ceramic forms, and a study of La2O 3 addition on phase formation, microstructures and electrical properties was investigated which are especially important from the viewpoint of the development of practical piezoelectric materials. The effect of La 2O3 addition was characterized on microstructure and electrical properties of PZN-PZT. Amounts of 0.05-1 wt% La2O 3 were doped on 0.2PZN-0.8PZT. All compositions of powders were uniaxially pressed in pellets and sintered at the temperature 1250°C with dwell time 2 h. Phase and microstructure development, dielectric and ferroelectric properties of ceramics were characterized by XRD, SEM, LCR meter and Modified Sawyer-Tower Circuit respectively. In addition, the values of permittivity maximum and the temperature of permittivity maximum were substantially decreased by La-doping and these results show increased Pr, P s and strain level but decreased Ec. © 2013 Copyright Taylor and Francis Group, LLC.